New Edition of the EAEU Good Pharmacovigilance Practice: What Has Changed? - D. A. Rozhdestvensky (Ministry of Health of the Russian Federation, Federal State Budgetary Institution «Scientific Centre for Expert Evaluation of Medicinal Products», 2023)
In late 2016, the Council of the Eurasian Economic Commission adopted the first version of the Rules of Good Pharmacovigilance Practice of the Eurasian Economic Union (EAEU GVP Guideline) based on a similar pharmacovigilance guidance published in the EU in 2014. By Decision No.81 of 19.06.2022, the Council of the Eurasian Economic Commission has amended the EAEU GVP Guideline, and the new version has been effective since 06.12.2022. The amendment has introduced a major revision to the terminology and significant changes to the sections on the risk management system and on organisation of safety information and signal management. The current EAEU GVP Guideline includes new subsections and a reviewed procedure for submitting pharmacovigilance documents to the regulatory authorities.In this interview, we have discussed the importance of the newly introduced pharmacovigilance changes in EAEU member states for the pharmaceutical industry with Dmitriy A. Rozhdestvensky, Candidate of Medical Sciences, Head of the Section of Coordination of Activities in the Sphere of Circulation of Medicines and Medical Products of the Technical Regulation and Accreditation Department of the Eurasian Economic Commission.